Предмет: Математика,
автор: nastenka451
0,4(х-3)-1,6=5(0,1х-0,5)
Ответы
Автор ответа:
2
0,4х-1,2-1,6=0,5х-2,5
-0,1х=0,3
х=-3
-0,1х=0,3
х=-3
abdulya16d:
перерешай, не правильно
Автор ответа:
14
0,4(х-3)-1,6=5(0,1х-0,5)
0,4х-1,2-1,6=0,5х-2,5
0,4х-0,5х=-2,5+1,2+1,6
-0,1х=0,3
х=0,3 : (-0,1)
х= -3
0,4х-1,2-1,6=0,5х-2,5
0,4х-0,5х=-2,5+1,2+1,6
-0,1х=0,3
х=0,3 : (-0,1)
х= -3
Похожие вопросы
Предмет: Русский язык,
автор: golga53
Предмет: Қазақ тiлi,
автор: Аноним
Предмет: Русский язык,
автор: валя263
Предмет: История,
автор: morozovav2006
Предмет: Физика,
автор: lilparty4